Exposure to Indoor Tanning Without Burning and Melanoma Risk by Sunburn History - Vogel, Rachel Isaksson (Oxford University Press, 2014)
Indoor tanning is carcinogenic to humans. Individuals report that they tan indoors before planning to be in the sun to prevent sunburns, but whether skin cancer is subsequently reduced is unknown. Using a population-based case–control study, we calculated the association between melanoma and indoor tanning after excluding exposed participants reporting indoor tanning–related burns, stratified by their number of lifetime sunburns (0, 1–2, 3–5, >5). Confounding was addressed using propensity score analysis methods. All statistical tests were two-sided. We observed increased risk of melanoma across all sunburn categories for participants who had tanned indoors without burning compared with those who never tanned indoors, including those who reported zero lifetime sunburns (odds ratio = 3.87; 95% confidence interval = 1.68 to 8.91; P = .002). These data provide evidence that indoor tanning is a risk factor for melanoma even among persons who reported never experiencing burns from indoor tanning or outdoor sun exposure.